Analisis Pengaruh Luas Lahan, Modal dan Tenaga Kerja Terhadap Hasil Produksi Pepaya Kalifornia di Desa Naena Muktipura (SP VI) - Sari, Desi Ratna; Tuasela, Antje (Journal of Economics and Regional Science, 2022)
this study aims to determine the effect of land area, capital and labor on papaya production in Naena Muktipura Village (SP VI) either partially or simultaneously. The method used by the researcher is the associative method. The data collection technique carried out by the researcher was distributing questionnaires which were distributed to 27 respondents. The analytical tool used in this research is multiple linear regression analysis. The results showed that partially land had no significant effect on papaya production in Naena Muktipura Village, Capital had a significant effect on papaya production in Naena Muktipura Village and labor had no significant effect on papaya production results in Naena Muktipura Village, meanwhile simultaneously the factors land production, capital and labor have a significant effect on papaya production in Naena Muktipura Village.